The mediating Role of Reflective Functioning Dimensions in the Relationship Between Parental Insecure Attachment Styles and Parenting Stress in Parents of Child with Attention Deficit-Hyperactivity Disorder - haniyeh mohammadi; zahra naderi nobandegani; samaneh asadi; tahereh sadeghiyeh (Ravānshināsī-i Afrād-i Istis̠nāyī, 2023)
AbstractThe aim of this study is to investigate the mediating role of the dimensions of reflective functioning in the relationship between insecure attachment styles and parenting stress in parents of child with attention deficit/hyperactivity disorder. The method of the current research was correlation-structural equation modeling and the research population included parents of children with attention deficit/hyperactivity disorder in Yazd city in 1401. Among them, the sample consisted of 295 fathers and mothers of these children selected using convenient method and fulfilled the questionnaires of experience of close relationships by Brennan et al. (1998), Parental reflective functioning by Luyten et al. (2017) and parents stress by Abidin (1995), in person or online. In the next step the data was analyzed using the statistical method of path analysis and multi-group analysis. The findings of the research showed that in both groups of mothers and fathers, pre-metallization can play a mediating role in the relationship between insecure anxious attachment style and parenting stress in fathers and mothers of children with attention deficit/hyperactivity disorder. Also, multi group analysis confirmed the role of parents' gender, and in the difference between these two groups, the path of avoidant attachment to parenting stress was significant in the mothers' group as opposed to the fathers' group. As a result, according to the findings, it can be said that in both groups of mothers and fathers, anxious attachment plays an important role in increasing pre-mentalization about children with disorders and thus increases the stress of parenting.Keywords: attention deficit/hyperactivity disorder, parenting stress, Parental reflective functioning, insecure attachment style.  Extended Abstract IntroductionAttention deficit hyperactivity disorder (ADHD) is one of the most common developmental neurodevelopmental disorders in childhood. Children with ADHD show more and more vigorousness, hyperactivity, neglect and sudden behaviors than normal children, and parents of these children often report high hopelessness in trying to manage their behavior. The researchers found that parents with children with attention deficit hyperactivity disorder experienced significantly more parental stress than parents with a child with normal development. In addition to these factors, parental attachment style affects their ability to cope with stress, and consequently these styles may also affect the stress of parents.At the same time, one of the important variables that can play a role in the relationship between parental attachment style and parenting stress is reflective functioning. It combines the concept of psychoanalysis of mind-set and attachment theories and refers to the ability of parents or caregivers to imagine their child's mental states such as their feelings, wishes, and desires.In general, the research question is whether the dimensions of reflective functioning can play the mediating role in the relationship between insecure attachment styles and parental stress in parents of children with attention deficit hyperactivity disorder? Literature Research The dominant model of parental stress identifies two main components: the child's domain, which originates directly from the child's characteristics, and the parent domain, which is most influenced by the parents' own performance. Overall stress is a combination of parent and child stress. Studies on families of children with ADHD show that parental stress increases in both areas. Parents who experience extreme levels of parental stress may be less able to take steps to help their child.Attachment theory holds that people's attachment systems are activated in stressful situations, such as when a child is afraid, or in pain, seeks to be close to his or her parent and feels relaxed in this way. Adult attachment can be described by two dimensions, anxious attachment and avoidance attachment. According to research, low maternal score in avoidant and anxious attachment styles is associated with higher resiliency against children with attention deficit hyperactivity disorder.The concept of reflective functioning combines the concept of psychoanalytic mentalization and attachment theories and refers to the ability of parents or caregivers to imagine their child's mental states such as their feelings, wishes, and desires. The three key dimensions of parental reflective functioning include: methods of pre-mentalization, confidence in state of mind and interest and curiosity.The first dimension, the state of pre-mentalization, refers to a non-subjective position that is often characteristic of parents with severe impairments in parental reflective functioning. The second dimension, certainty of mental states , refers to parents' ability to recognize that mental states are inherently ambiguous. The third dimension refers to the parents' curiosity and interest in the child's state of mind, i.e., the parents' willingness to understand the child. Studies that have evaluated parents' reflective capacity indicate that parents' ability to mentalize can be an important factor for tolerance of neonatal distress, reinforcement of more positive discipline strategies and less parental stress perception. Regarding the difference between parents and mothers, in some studies, mothers were more likely than fathers to believe that their children with attention deficit hyperactivity disorder were stressful. MethodologyThe present study was conducted by correlation-structural equation modeling. The statistical population consisted of mothers and fathers of children with attention deficit hyperactivity disorder living in Yazd city in 1401 and the sample consisted of 295 parents who were selected using convenient method. After collecting the questionnaires, AMOS-24 and SPSS-24 software were used for data analysis. In addition, descriptive statistics (mean, standard deviation), correlation coefficients, multi-group analysis and index of fit were used to investigate the research question. The research instruments included the Experiences of Close Relationships, Parental Reflective Functioning Questionnaire and Parents Stress Questionnaire.  ResultsThe results showed that in both groups of mothers and fathers, only the correlation coefficients of pre-mentalization scale with parenting stress (r=0.55 and fathers: r=0.50) were significant. Also, the correlation coefficient of insecure attachment anxiety with parenting stress was significant for both groups (r=0.56 and fathers: r=0.40) while insecure avoidance attachment correlation coefficient (mothers: r=0.22) was significant only for mothers. Therefore, for better fit, non-significant pathways were removed from the model and without these two subscales the models were fitted. Then, in the form of mediation model, pre-mentalization was shown in relation between the variables of the research.Mediation Model of Parental Pre-Mentalization in the Relationship between Insecure Attachment Styles (Anxiety/Avoidance) and Fathers' Parenting Stress  According to the form of avoidance, attachment pathway to parental stress (β =-0.04) and pre-mentalization (β =-0.09) is non-significant. On the other hand, the attachment pathways of anxiety to pre-mentalization (β=0.47), anxiety attachment to parenting stress (β=0.26) and pre-mentalization to parenting stress (β=0.38) are significant.Mediation Model of Parental Pre-mentalization in the Relationship between Insecure Attachment Styles (Anxiety/Avoidance) and Parental Stress of Mothers According to mothers' model, avoidance attachment to pre-mentalization (β=0.05) is not significant. On the other hand, avoidant attachment pathways to parenting stress (β=0.17), anxiety attachment to pre-mentalization (β=0.53), anxiety attachment to parenting stress (β=0.37) and pre-mentalization to parenting stress (β=0.36) are significant. In order to improve the overall fitness of two models of parents and mothers, the model was modified by applying the covariance between avoidant attachment and anxious attachment and the results of fitting the model before and after the modification were brought. According to the results of fit, it seems that regression weights make a difference in at least some pathways between the fit of mothers and fathers. Therefore, the role of parents' gender in the research model was confirmed. DiscussionIn explaining this finding, it can be said that considering that reflective functioning is the operationalization of mental processes that reinforces the capacity of mentalization. When parents are able to understand the meaning and purpose of their child's signals, it gives a more appropriate response, thus forming a reflective functioning or ability to perceive oneself and others in mental states such as thoughts, feelings, and intentions. So parents who reflect are able to understand their child's behaviors according to mental states. Similarly, in dealing with children, they experience less stress caused by confusion in behavior and dealing with the child. Parents who are not able to build capacity in this area will have more stress. ConclusionInsecure attachment (especially anxious attachment) seems to cause serious disorders in parental pre-mentalization and because parents with this style cannot understand a child with attention deficit hyperactivity disorder, they experience high stress. AcknowledgementWe need to thank all the people who helped us in this study, especially parents of children with ADHD and also members of Dr. Tahereh Sadeghiye Psychiatric Clinic.  * Corresponding Author: zahra.naderi@yazd.ac.irHow to Cite: Saeed, M., Saeed, M., Saeed, M. ‌(2024). The Mediating Role of Parental Reflective Functioning Dimensions in the Relationship Between Parental Insecure Attachment Styles and Parenting Stress in Parents of Children With Attention Deficit-Hyperactivity Disorder, Journal of Psychology of Exceptional Individuals, 13(52), 1-29. DOI: 10.22054/jpe.2023.74893.2602